DOI: 10.31274/rtd-180813-13421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary glycolytic inhibitors on pork quality

Abstract: This manuscript has been reproduced from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in type vriter face, while others may be from any type of computer printer.The quality of this reproduction Is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
2

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
1
0
2
Order By: Relevance
“…In addition, there were no significant differences on the water holding capacity, drip loss, cooking loss and surface color of sample. These results mean that the dietary quercetin treatments did not change the physical meat quality characteristics, which is in agreement with Kremer et al (2000).…”
Section: Proximate Compositionsupporting
confidence: 80%
“…In addition, there were no significant differences on the water holding capacity, drip loss, cooking loss and surface color of sample. These results mean that the dietary quercetin treatments did not change the physical meat quality characteristics, which is in agreement with Kremer et al (2000).…”
Section: Proximate Compositionsupporting
confidence: 80%
“…The meat color a* values were lowered by dietary OE, although there was no dose dependent manner. In a pig feeding study [30], dietary quercetin decreased a* value of pork. However, there are other studies [8,21] that reported either no or inconsistent effect by dietary onion or quercetin on meat color.…”
Section: Discussionmentioning
confidence: 99%
“…Однако конечное значение pH через 24 ч после убоя не зависело от рациона. Отмечено повышение влагосвязывающей способности мяса и снижение потерь массы при хранении в условиях розничной торговли в течение 12 сут (69). Адаптогены (дигидрокверцетин в дозе 3,5 мг/кг живой массы и лепестки роз в дозе 0,255 мг/кг живой массы) способствовали снижению накопления первичных и вторичных продуктов окисления липидов в процессе хранения как в мышцах, так и в жире.…”
unclassified
“…Незначительный положительный эффект отмечен по рН и цвету свинины (67,70). Установлены эффективные для свиней дозы кверцетина -25-50 мг/кг массы животного (55, 58) и дигидрокверцетина -1 мг/кг массы животного (64-66) и 3,5 мг/кг живой массы (67,70), а также факт, что флавоноиды эффективны при скармливании как в процессе роста животных (55,65), так и непосредственно перед убоем, транспортировкой (68,69,71).…”
unclassified